Evolutionary Basis of Human Running and Its Impact on Neural Function - Schulkin, Jay (Frontiers in Systems Neuroscience, 2016)
Running is not unique to humans, but it is a seemingly basic human capacity. This paper addresses the evolutionary origins of humans running long distances, the basic physical capability of running, and the neurogenesis of aerobic fitness. This paper more specifically speaks to the conditions that set the stage for the act of running, and then looks at brain expression, and longer-term consequences of running within a context of specific morphological features and diverse information molecules that participate in our capacity for running and sport. While causal factors are not known, we do know that physiological factors are involved in running and underlie neural function. Multiple themes about running are discussed in this paper, including neurogenesis, neural plasticity, and memory enhancement.